Exploring factors affecting life dissatisfaction in edlerly - KIM, Kye Chul (KDI School, 2017)
The aging of the world’s population, and the issues that each nation is facing as its aging citizens increase in number, is receiving increasing attention from the media, government and policy-making officials, international. Since Korea is moving towards the aged society, increasing is the social attention on overall depression and life dissatisfaction of the elderly. The purpose of this study is to find the factors affecting depression of elderly among demography characteristics of aged people, categorized dissatisfactions and sources of income, based on the 2014 national survey data of the actual living condition of the elderly and welfare need. We found that many factors have significant impact on the depression of the elderly, such as socio-demographic characteristics, the level of economic, social, physical, children relative dissatisfactions. Path analysis was utilized to identify the links and pathways between these factors and examine their impact on quality of life for people with depression.
Thesis(Master) --KDI School:Master of Public Management,2017